Cotton-based development in Sub-Saharan Africa? Global commodity chains, national market structure and development outcomes in Burkina Faso, Mozambique and Tanzania - Cornelia Staritz; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2015)
Cotton is one of the most important cash crops in Sub-Saharan Africa (SSA) and has had an important role in job creation, poverty reduction and foreign exchange generation. SSA cotton exporters face particularly three interconnected challenges - how to increase yields and quality in the context of small holder farming; how to deal with volatile international prices; how to increase value addition through local processing. This paper analyses the cotton sectors in Burkina Faso, Mozambique and Tanzania along these challenges focusing on dynamics in global cotton commodity chains, different national market structures and related development outcomes. The aim of the paper is not to identify the best cotton sector organisation model but to point out issues that are important for positive development outcomes. The analysis shows that the more regulated systems in Burkina Faso and Mozambique generally outperform the liberalized system in Tanzania in terms of production levels, yields, input provision, and price stability. But there are also major differences among the more regulated systems with Burkina Faso faring substantially better in yields and farmers' price share. The state, however, also bears a greater risk in Burkina Faso through its involvement in the largest cotton company and the stabilisation fund. The system in Tanzania provides similar farmers' price shares as in Burkina Faso albeit with higher price instability and inequality. Tanzania has been further most successful in value addition which, however, cannot be attributed to the cotton sector market structure but primarily to a stronger manufacturing tradition. The institutional context in the cotton sector, particularly strong and independent farmers' associations, have a crucial role in all models to ensure that farmers' interests are respected.
Keywords: 330; commodity-based development; cotton; price instability; value addition; Burkina Faso; Mozambique; Tanzania